Numerical simulation and analysis of flow field in directional solidification equipment. Issue 1 (1st December 2022) - Cheng Zhang, Zhi; Sun, Hui; Wen, Ning; Liu, Tao
Abstract: Directional solidification equipment is an efficient purification tool. In this paper, the geometric model was established based on the equipment, and the numerical simulation of the flow field in equipment was realized through the RNG turbulence model, flow volume function model, and the multiple reference system method. In order to improve the fluid velocity, turbulent kinetic energy, and uniform distribution of circulating flow in the flow field, the effects of different crucible structures, process parameters, and structure of rotator on the flow field were analyzed. The research results show that the round bottom crucible has a faster flow velocity in front of the wall, and the flow velocity distribution is uniform. When the rotator is located in the center of the flow field, flow velocity and turbulent kinetic energy are distributed more evenly. Controlling the rotational speed to reduce the air entering the liquid phase is conducive to preventing solidification from being oxidized. Considering the thickness of the solidified layer, increasing the blade length can help increase the fluid velocity.